Co-detection of measles virus vaccine strain and seasonal coronavirus in an immunocompromised patient with pneumonia - C. Anderson; R. Odrobina; L. T. Murugan; B. T. Bradley (ASM Case Reports, 2026)
ABSTRACT Background Measles vaccination is recommended for hematopoietic stem cell transplant (HSCT) recipients ≥24 months post-transplant in the absence of graft-versus-host disease and immunosuppressive therapy. Administration of live vaccines during immunosuppression may result in iatrogenic injury. Case Summary We describe a 76-year-old patient with stage 3 multiple myeloma who had undergone autologous HSCT and received multiple therapies, including chimeric antigen receptor T-cell therapy and recent daratumumab treatment. Approximately 1 month after measles, mumps, and rubella (MMR) vaccination, she presented with progressive respiratory symptoms and hypoxia. Despite broad-spectrum antimicrobials and supportive care, her condition deteriorated, requiring ICU admission and mechanical ventilation. Molecular testing of her bronchoalveolar fluid detected the measles virus vaccine strain and seasonal coronavirus OC63. The patient succumbed to her illness on hospital day 16. Conclusion This case highlights the rare but severe complication of measles vaccine-associated pneumonia in an immunocompromised host. While guidelines support MMR vaccination ≥24 months post-HSCT, ongoing immunosuppression may increase susceptibility to vaccine-related adverse events. Rising measles incidence in North America underscores the need for individualized vaccination strategies, balancing infection risk and vaccine safety. Healthcare providers should exercise caution when considering live-attenuated vaccines in HSCT recipients with recent immunosuppressive therapy. Further research is needed to refine vaccination guidelines for this vulnerable population.